Detection of Human Bocavirus Type 1 infection in Panamanian children with respiratory illness. Issue 3 (19th October 2015) - Moreno, Brechla; Abrego, Leyda; Carrera, Jean‐Paul; Franco, Danilo; Gaitán, Melissa; Castillo, Juan; Pascale, Juan M.; Arbiza, Juan
Abstract : The human bocavirus (HBoV) was added as a new member of the Parvoviridae family in 2005 upon its discovery in nasopharyngeal aspirates from children with respiratory infection. Recently, there has been increasing evidence of worldwide circulation of HBoV; however, in Latin America few studies have been conducted. In order to detect the circulation of HBoV in Panama, based on the National Flu Surveillance System, we developed this retrospective, cross‐sectional study, from January 2011 to January 2012. Children younger than 6 years old who presented with respiratory disease were enrolled in this study. Nasopharyngeal swabs were taken in sentinel surveillance sites. Samples were tested to detect mRNA from HBoV, as well as viral RNA and DNA from others respiratory viruses. A total of 1078 patients were enrolled in this study. Overall, 44 (4.1%) of the patients presented HBoV. The most common symptoms were cough (84.6%), fever (82.1%), rhinorrhea (74.4%), and sore throat (38.5%). Less than half (45.5%) of HBoV infected patients presented with monoinfection while 54.5% of cases presented with coinfection with others respiratory viruses. Both, outpatients and inpatients were included in this study. Outpatients corresponded to 52.3% of the cases and 47.7% were inpatients. Coinfection was observed in the 50% of the inpatient cases. Phylogenetic analyses indicated that the circulating strains belonged to different clades of HBoV genotype 1. Taken together, our results support the pathogenic nature of this viral agent, especially in younger children. J. Med. Virol. 88:389–394, 2016 . © 2015 Wiley Periodicals, Inc.